Lacosamide modulates collapsin response mediator protein 2 and inhibits mossy fiber sprouting after kainic acid-induced status epilepticus. Issue 16 (7th November 2018) - Wang, Xue; Yu, Yang; Ma, Rui; Shao, Na; Meng, Hongmei
Abstract : Mossy fiber sprouting (MFS) and neuronal loss are important pathological features of chronic epilepsy closely related to the development of spontaneous recurrent seizures. However, the pathological mechanism of MFS remains unclear. Collapsin response mediator protein 2 (CRMP2) is a cytoplasmic protein highly expressed in the nervous system and is involved in axon/dendrite specification and axonal growth. It is possibly associated with the development of MFS. Lacosamide (LCM), a novel antiepileptic drug, was recently found to inhibit the CRMP2-mediated neurite outgrowth. Therefore, we studied the relationships between LCM, CRMP2, and MFS, seeking potential therapeutic targets for epileptogenesis and a better understanding of the mechanism of action of LCM. We used kainic acid to induce status epilepticus in an animal model and examined the resultant changes in protein expression by Western blot and changes in histology by specific staining for cell death and MFS. Our results showed that the expression level of CRMP2 was elevated and the expression level of phosphorylated CRMP2 (p-CRMP2) was reduced following status epilepticus. Administration of LCM not only reversed this effect but also suppressed spontaneous recurrent seizures and reduced MFS and loss of hippocampal neurons. This study reveals that, in addition to its antiseizure efficacy, LCM has a neuroprotective effect and inhibits the development of epilepsy. CRMP2 is possibly involved in the mechanism by which LCM suppresses MFS and is expected to be a new therapeutic target for treating epileptogenesis.